Impact of Energy Price Volatility on Financial Stability and Industrial Growth in Nigeria - Jamiu Adeniyi Yusuf; Saka Fatai Adio; Babalola Abubakar Akorede (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: Energy price volatility is a critical macroeconomic challenge for resource-dependent economies like Nigeria, with potential implications for financial stability and industrial development. Despite the centrality of energy to production and investment decisions, empirical evidence on how fluctuations in energy prices interact with financial stability and industrial growth in Nigeria remains limited.Objective: This study examines the effects of energy price volatility on financial stability in Nigeria. Also, the role of industrial growth and exchange rate movements in shaping financial stability outcomes in Nigeria.Methods: The study employed annual time-series data for Nigeria, with Autoregressive Distributed Lag (ARDL) to capture both short-run and long-run relationships among the variables. Financial stability was modelled as a function of energy price volatility, industrial growth, and the exchange rate. Bounds testing was conducted to establish long-run relationships, while error correction mechanisms were used to analyse short-run.Results: Findings reveal that energy price volatility exerts a negative effect on financial stability in both short and long run, indicating fluctuations in energy prices undermine Nigeria’s financial system. Contrariwise, industrial growth shows a positive relationship with financial stability, suggesting that increased industrial activity enhances resilience against energy price shocks. The exchange rate also exhibits a negative and significant effect on financial stability, showing Nigeria’s susceptibility to external economic disturbances.Conclusion: The results shows that stabilising energy prices and strengthening industrial capacity are critical for safeguarding financial stability in Nigeria. Recommendation includes, the adoption of energy price stabilisation policies, accelerated industrialization strategies, and a managed exchange rate regime.